Balancing Digital Innovation and Spiritual Pedagogy: A Critical Integrative Review of Artificial Intelligence in Islamic Religious Education - Herina Yanti; Zulfani Sesmiarni; Rika Sri Yulianti (Suluah Pasaman, 2026)
This article examines the integration of artificial intelligence (AI) in Islamic Religious Education (PAI) in Indonesia with a focus on balancing digital technology innovation and spiritual pedagogical values. This research uses systematic literature review of 47 publications from various accredited national and international journals between 2019–2024. The results of the study indicate that: (1) The use of AI in PAI can increase the efficiency of competency-based learning by up to 34%, but has the potential to reduce the affective-spiritual dimension if not managed properly; (2) There is a significant digital divide between Islamic educational institutions in urban and rural areas; (3) A hybrid model between machine intelligence and local wisdom based on Islamic boarding schools has proven effective as a bridge between modernity and tradition; and (4) The competence of PAI teachers in digital literacy is a determining factor in the success of AI implementation. This study recommends the development of an integrative pedagogical framework that positions AI as a tool (tawassul) that does not replace the spiritual and humanistic dimensions in PAI. Theoretical and practical implications for the development of national Islamic education curriculum and policies are also discussed comprehensively.